Gradual Increase in Lung Cancer Risk Due to Particulate Matter Exposure in Patients With Pulmonary Function Impairments: A Nationwide Korean Database Analysis - Lee, Jongin; Choi, Joon Young; Lim, Jeong Uk (Journal of Korean medical science, 2025)
Lung cancer remains a significant public health concern, with external environmental factors, such as particulate matter 2.5 (PM2.5), playing a crucial role in its development. This study aimed to assess the interaction between cumulative exposure to PM2.5 and lung function impairment, focusing on the risk of lung cancer in a large Korean population. Data from the Korea National Health and Nutrition Examination Survey from 2007 to 2020 were analyzed with linkage of the national cancer registry. A total of 43,973 participants, including 386 lung cancer cases, were included, with spirometry data available to classify lung function into categories. PM2.5 exposure was quantified using geocoded address information. Logistic regression models with interaction terms were used to evaluate lung cancer risk according to PM2.5 exposure levels and in interaction of lung function categories. A significant increase in lung cancer risk was observed with higher PM2.5 exposure levels, with odds ratios (ORs) of 1.41, 1.59, and 1.68 for the 2nd, 3rd, and 4th quartiles, respectively in multivariable models. Stratified analysis showed that the interaction between PM2.5 exposure and obstructive lung function significantly increased lung cancer risk, with ORs of 2.74 for spirometric obstruction and 3.43 for preserved ratio impaired spirometry in the highest PM2.5 quartile. This study suggests the carcinogenic risk of PM2.5 exposure, particularly in individuals with obstructive lung function impairments.